Hukum Pernikahan di Kesultanan Melaka Abad ke-15 dan ke-16 M - Ayang Utriza Yakin (Ulumuna, 2015)
This article examines legal aspects of Marriage law in the Sultanate of Malaka in the 15th and 16th centuries. It focuses on some legal aspects of Undang-undang Melaka (a text of laws of Melaka) represented by Liaw Yock Fang, regarding the issues of marriage such as wali (marriage guardian), ijāb-qabūl (consent of both parties), witness(es), t\alāq (repudiation), faskh (broken marriage contract), interfaith marriage and marrying slave. This study aims to know the source of the marriage laws of Undang-Undang Melaka (UUM). It shows that UUM was a collection of common law in Melaka and consisted of Islamic law. One aspect of Islamic laws was marriage law. In UUM, the legal aspect was based on fiqh of several schools (madhhab), particularly the al-Shāfi‘ī school derived from al-Iqnā’ written by al-Sharbini. This finding also refuses the previous research finding stating that it was derived from al-Taqrīb by Abū Shujā‘. DOI: http://dx.doi.org/10.20414/ujis.v19i1.1248